Premix and method for producing cosmetic composition, cosmetic composition, method for surface photoprotection and use of premix

The premix prepared by using niobium nanoparticles with a crystallinity of at least 26% is solved by solving the application of existing physical photoprotectants on the skin, achieving efficient UV radiation protection and improving the sensory of cosmetics.

CN120225164APending Publication Date: 2025-06-27INSTITUTO HERCILIO RANDON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380080220.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-05
Filing Date
2023-10-05
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

Existing physical light protectors such as titanium dioxide have problems such as whitening, paste-like, poor application and incompatible with cosmetic carriers on the skin. At the same time, titanium dioxide is banned by the EU in the food industry.

Method used

Premixes are prepared using niobium nanoparticles containing at least 26% crystallinity for the production of an improved cosmetic composition that has high light protection and is suitable for the surface of individual skin against UV radiation.

Benefits of technology

The highlight protection ability and cosmetic sensory advantages are achieved, the disadvantages of titanium dioxide are avoided, and the substrate is not affected, and the mixing process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120225164A_ABST
    Figure CN120225164A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of beauty and related science. More specifically, the present invention relates to a premix for producing a cosmetic composition, a method for producing a cosmetic composition and an improved cosmetic composition. Furthermore, it defines a method for photoprotection of a surface, and the use of the premix for the preparation of a cosmetic composition for photoprotection of a skin surface of an individual against UV radiation. The premixes and compositions of the present invention comprise niobium nanoparticles and provide advantageous and surprising effects, including high light protection capability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention belongs to the field of beauty and related sciences. More specifically, the present invention relates to a premix for producing a cosmetic composition, a method for producing a cosmetic composition, and an improved cosmetic composition. It also defines a method for surface photoprotection, and the use of the premix for preparing a cosmetic composition for anti-UV radiation photoprotection of an individual's skin surface. The premix and composition of the present invention contain niobium nanoparticles and provide advantageous and surprising effects, including high photoprotection ability. BACKGROUND ART

[0002] Among the physical sunscreens available on the market, titanium dioxide is the most commonly used, followed by zinc oxide and hydroxyapatite. In 2019, this ingredient had a market share of 14.5 million euros in all its applications; it is a dye used as a whitening agent in cosmetics, food, pharmaceuticals, and paints.

[0003] Although physical sunscreens are the most common physical sunscreens, this ingredient has problems such as a whitened appearance on the skin, a pasty feel, poor spreadability, and incompatibility with some cosmetic carriers. In addition, titanium dioxide has been banned in the food industry in the European Union because it is a potentially carcinogenic ingredient.

[0004] The present invention provides an alternative method that solves these problems and also has additional advantages.

[0005] Patent document JP2003267850A discloses the use of a powder dispersion (premix) including nanoparticles in a cosmetic composition (more specifically, a sunscreen). On the other hand, the document does not disclose the premix or composition having specific features of the present invention.

[0006] Patent document WO2021121647A1 discloses the use of a composite metal material suitable for a cosmetic composition, such as a sunscreen that improves the UV absorption process. On the other hand, the document only generally discloses several examples, without specific tests, and does not disclose the premix or composition having specific features of the present invention.

[0007] Patent document WO2007133808A2 discloses the use of nanoparticles in a cosmetic composition. However, the document does not disclose the premix or composition having specific features of the present invention.

[0008] The article by Ali et al. (01 / 2022) (Use of niobium oxide nanoparticles as nanofillers in PVP / PVA blends to enhance UV–visible absorption, opto-linear, and nonlinear optical properties) discloses the use of niobium pentoxide nanoparticles to improve UV absorption properties. On the other hand, the document does not disclose the premix or composition with specific features of the present invention.

[0009] The article by Lyu et al. (08 / 2022) (Nanoparticles in sunscreen: exploration of the effect and harm of titanium oxide and zinc oxide) introduces the use of nanoparticles in sunscreen. On the other hand, the article only discusses the effects of titanium oxide and zinc oxide and does not disclose the premix or composition with specific features of the present invention.

[0010] Based on what can be inferred from the retrieved literature, no document is found that anticipates or implies the teachings of this creation / secret / invention. In the view of the inventors, the invention disclosed herein is novel and creative compared to the prior art. Summary of the Invention

[0011] The present invention provides a premix for producing a cosmetic composition, a method for producing a cosmetic composition, and an improved cosmetic composition. Among them, the premix and composition of the present invention contain a certain mass of niobium nanoparticles. In one embodiment, the mass of niobium nanoparticles contains at least 26% crystallinity. The present invention also defines a method for surface photoprotection and the use of the premix for preparing a cosmetic composition for anti-UV radiation photoprotection of an individual's skin surface.

[0012] In one embodiment, the premix can be prepared as a stable colloidal suspending agent, so there are subsequent advantages for those who add it to cosmetic formulations. This advantage is achieved by reducing the mixing time and is not affected by the substrate because these premixes are different from TiO2 and other available materials applied as dry powders, which require expensive and laborious dispersion steps when incorporated into the final cosmetic mixture.

[0013] In the context of the present invention, the expression "niobium nanoparticles" encompasses a variety of niobium-containing chemical entities, including metallic niobium, niobium oxides, niobium hydrates, niobium hydrides, niobium carbides or nitrides, ferro-niobium or alloys of niobium with other metals or transition metals, or combinations thereof. It also includes niobium pentoxide (Nb2O5), NbO2, and NbO.

[0014] In one embodiment, the niobium nanoparticles of said mass preferably comprise at least 41% crystallinity, preferably comprise at least 61% crystallinity, and even more preferably comprise at least 80% crystallinity.

[0015] It is worth adding that the product can also contain other Nb polymorphs in addition to Nb2O5, such as NbO2 and the amorphous forms of these same crystal phases, as well as different combinations and ratios thereof. Example: A premix can be prepared with 98% partially crystalline and amorphous Nb2O5 + 2% NbO2. In this case, 66% of the composition is crystalline. For another composition, a premix can be prepared with 87% Nb2O5 + 13% NbO2. In this case, 95% of the composition is amorphous.

[0016] In one embodiment, niobium pentoxide has proven to be an excellent substitute for titanium dioxide due to its physicochemical properties. In the present invention, product LN10 (an emulsion containing various versions of niobium pentoxide particles For example, particles treated for 1 h, 6 h, and 12 h, as well as particles with micron and submicron diameters) was evaluated for UVA and UVB photoprotection and showed advantages over products containing titanium dioxide, zinc oxide, and nano-hydroxyapatite. The product of the present invention provides benefits comparable to those of titanium dioxide in terms of photoprotection and has advantages in terms of cosmetic sensorial aspects, etc.

[0017] These and other objects of the present invention will be immediately appreciated by those skilled in the art and companies interested in this sector and will be described in sufficient detail in the following specification to enable reproduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The following figures are shown:

[0019] Figure 1 The results of the particle size distribution analysis showing the counting frequency (%) by diameter (nm) of the sample with a treatment time of 1 h.

[0020] Figure 2 The results of the particle size distribution analysis showing the counting frequency (%) by diameter (nm) of the sample with a treatment time of 3 h.

[0021] Figure 3Shows the particle size distribution analysis results of the count frequency (%) of the sample with a processing time of 6 h by diameter (nm).

[0022] Figure 4 Shows the particle size distribution analysis results of the count frequency (%) of the sample with a processing time of 12 h by diameter (nm).

[0023] Figure 5 Shows the particle size distribution analysis results of the percentage of number density (%) of the sample with a processing time of 6 h by size category (μm).

[0024] Figure 6 Shows the particle size distribution analysis results of the percentage of volume density (%) of the sample with a processing time of 6 h by size category (μm).

[0025] Figure 7 Shows the particle size distribution analysis results of the percentage of number density (%) of the sample with a processing time of 12 h by size category (μm).

[0026] Figure 8 Shows the particle size distribution analysis results of the percentage of volume density (%) of the sample with a processing time of 12 h by size category (μm).

[0027] Figure 9 Shows the comparison results between the curves of niobium pentoxide nanoparticle samples with a processing time of 6 h obtained by comparing the numerical distribution and the volume distribution as described in Example 1.

[0028] Figure 10 Shows the comparison results between the curves of niobium pentoxide nanoparticle samples with a processing time of 12 h obtained by comparing the numerical distribution and the volume distribution as described in Example 1.

[0029] Figure 11 Shows the comparison results between the number density curves (%) of niobium pentoxide nanoparticle samples with processing times of 6 h and 12 h obtained by comparing the numerical distribution with a processing time of 6 h and the numerical distribution with a processing time of 12 h as described in Example 1.

[0030] Figure 12 Shows the comparison results between the volume density curves (%) of niobium pentoxide nanoparticle samples with processing times of 6 h and 12 h obtained by comparing the volume distribution with a processing time of 6 h and the numerical distribution with a processing time of 12 h as described in Example 1.

[0031] Figure 13Shows the comparative results of UVA and UVB tests for all samples / products. The following are shown: A) 5% LN10 6h emulsion; B) 10% LN10 6h emulsion; C) 5% LN10 12h emulsion; D) 10% LN10 12h emulsion; E) 5% zinc oxide emulsion; F) 5% nano-hydroxyapatite emulsion; G) 5% titanium dioxide emulsion.

[0032] Figure 14 Shows the comparative results of samples / products applied at 5% and subjected to UVA and UVB tests. The following are shown: A) 5% LN10 6h emulsion; B) 5% LN10 12h emulsion; C) 5% zinc oxide emulsion; D) 5% nano-hydroxyapatite emulsion; E) 5% titanium dioxide emulsion.

[0033] Figure 15 Shows the comparative results of LN 10 6h and LN 10 12h samples / products applied at 5% and 10% and subjected to UVA and UVB tests. The following are shown: A) 5% LN10 6h emulsion; B) 5% LN10 12h emulsion; C) 10% LN10 6h emulsion; D) 10% LN10 12h emulsion.

[0034] Figure 16 Is a set of two photos, namely, A) before applying the product 5% LN10 12h emulsion and B) after applying the product 5% LN10 12h emulsion, showing an immediate soft-focus effect for covering blemishes.

[0035] Figure 17 Shows a comparative graph of all the formulations tested in the present invention. Detailed Description

[0036] The present invention provides a premix for producing a cosmetic composition, a method for producing a cosmetic composition, and an improved cosmetic composition. Among them, the premix and composition of the present invention contain a certain mass of niobium nanoparticles. In one embodiment, the mass of niobium nanoparticles includes at least 26% crystallinity.

[0037] One of the objectives of the present invention is to provide a premix and a composition, the premix and composition providing a soft-focus effect, also known as a blurring effect, which is a soft covering effect that flattens the surface and reflects light so that we do not notice blemishes. The premix is used as a common makeup primer.

[0038] In one embodiment, the premix can be prepared as a stable colloidal suspension, thus presenting subsequent advantages for those who add it to cosmetic formulations. This advantage is achieved by reducing the mixing time, independent of the substrate, as these premixes are different from TiO2 and other available materials applied as dry powders, which require expensive and laborious dispersion steps when incorporated into the final cosmetic mixture.

[0039] One object of the present invention is a skin photoprotective cosmetic composition.

[0040] In the present invention, the composition contains niobium nanoparticles.

[0041] In the context of the present invention, the expression "niobium nanoparticles" includes various niobium-containing chemical entities, including metallic niobium, niobium oxides, niobium hydrates, niobium hydrides, niobium carbides or niobium nitrides, niobium iron or alloys of niobium with other metals or transition metals, or combinations thereof. It also includes niobium pentoxide (Nb2O5), NbO2 and NbO.

[0042] In the context of the present invention, the expression "crystallinity" should be understood as the degree to which a material predominantly has a single crystal phase or a polycrystalline phase rather than predominantly having an amorphous phase.

[0043] In one embodiment, the mass of the nanoparticles preferably comprises at least 5%, more preferably at least 10%, more preferably at least 15%, more preferably at least 20%, more preferably at least 26%, more preferably at least 30%, more preferably at least 35%, more preferably at least 40% crystallinity, more preferably at least 41%, more preferably at least 45%, more preferably at least 50% crystallinity, and even more preferably at least 55% crystallinity. In one embodiment, the crystallinity is at least 60%, more preferably at least 61%, more preferably at least 65%, more preferably at least 70%, more preferably at least 75%, more preferably at least 80%. In a non-limiting embodiment, the crystallinity is 26%, 41% or 61%.

[0044] In one embodiment, the mass of the niobium nanoparticles preferably comprises at least 41% crystallinity, preferably at least 61% crystallinity, and even more preferably at least 80% crystallinity.

[0045] It is worth adding that the product can also contain other Nb polycrystalline forms besides Nb2O5, such as NbO2, and the amorphous forms of these same crystal phases, as well as their different combinations and ratios. Non-limiting examples: A premix can be prepared with 98% partially crystalline and amorphous Nb2O5 + 2% NbO2. In this case, 66% of the composition is crystalline. For another composition, a premix can be prepared with 87% Nb2O5 + 13% NbO2. In this case, 95% of the composition is amorphous.

[0046] In one embodiment, a composition containing niobium pentoxide nanoparticles is designated LN10. In some embodiments, the composition contains up to 5 wt% or up to 10 wt% of the nanoparticles. In some embodiments, the niobium pentoxide nanoparticles have a particle size distribution spectrum that depends on the processing time. In some embodiments, the cases of 1-hour processing, 6-hour processing, and 12-hour processing are illustrated. The samples processed for 6 h and 12 h have the following particle size distribution spectra respectively: d10(6h) = 142 nm to 197 nm, d50(6h) = 208 nm to 343 nm, d90(6h) = 350 nm to 599 nm; d10(12h) = 80 nm to 129 nm, d50(12h) = 125 nm to 247 nm, d90(12h) = 230 nm to 435 nm.

[0047] The object of the present invention is a method for surface light protection, comprising at least one step of applying a cosmetic composition as defined above on at least one surface. In one embodiment of the method, the light protection is against UV radiation.

[0048] In one embodiment of the method, the surface is an object surface or a skin surface. In one embodiment, the surface is the surface of an individual's skin.

[0049] The object of the present invention is the use of the premix as described above for the production of a cosmetic composition for anti-UV radiation light protection on the surface of an individual's skin.

[0050] In the context of the present invention, the term "individual" should be understood as a human or an animal. In one embodiment, the individual can be understood as a human.

[0051] The present invention is also defined by the following clauses:

[0052] A premix for the production of a cosmetic composition containing one or more excipients and a certain mass of niobium nanoparticles, wherein the mass of the niobium nanoparticles has a crystallinity of at least 26%.

[0053] A premix as described above, wherein the mass of the nanoparticles preferably comprises at least 5%, more preferably at least 10%, more preferably at least 15%, more preferably at least 20%, more preferably at least 26%, more preferably at least 30%, more preferably at least 35%, more preferably at least 40% crystallinity, more preferably at least 41%, more preferably at least 45%, more preferably at least 50% crystallinity, and even more preferably at least 55% crystallinity. In one embodiment, the crystallinity is at least 60%, more preferably at least 61%, more preferably at least 65%, more preferably at least 70%, more preferably at least 75%, more preferably at least 80%. In a non-limiting embodiment, the crystallinity is 26%, 41% or 61%.

[0054] A premix as described above, wherein the mass of niobium nanoparticles preferably comprises at least 41% crystallinity, preferably comprises at least 61% crystallinity, and even more preferably comprises at least 80% crystallinity.

[0055] A premix as described above, comprising up to 80% by weight of niobium nanoparticles. This high concentration of nanoparticles facilitates the method of producing a cosmetic composition by distributing them in other ingredients / excipients.

[0056] In one embodiment, the premix consists of particles dispersed in an oil phase containing the ingredients / excipients.

[0057] A premix as described above, wherein the nanoparticles are niobium pentoxide and its particle size distribution is: d10 = 142 nm to 197 nm, d50 = 208 nm to 343 nm, d90 = 350 nm to 599 nm; d10 = 80 nm to 129 nm, d50 = 125 nm to 247 nm, d90 = 230 nm to 435 nm.

[0058] A method for producing a cosmetic composition, comprising at least one step of mixing a premix as described above into a cosmetic excipient.

[0059] A cosmetic composition comprises one or more excipients and a certain mass of niobium nanoparticles, wherein the mass of the niobium nanoparticles comprises at least 26% crystallinity.

[0060] The cosmetic composition as described above, wherein the nanoparticles by mass preferably comprise at least 5%, more preferably at least 10%, more preferably at least 15%, more preferably at least 20%, more preferably at least 26%, more preferably at least 30%, more preferably at least 35%, more preferably at least 40% crystallinity, more preferably at least 41%, more preferably at least 45%, more preferably at least 50% crystallinity, even more preferably at least 55% crystallinity. In one embodiment, the crystallinity is at least 60%, more preferably at least 61%, more preferably at least 65%, more preferably at least 70%, more preferably at least 75%, more preferably at least 80%. In one non-limiting embodiment, the crystallinity is 26%, 41% or 61%.

[0061] The cosmetic composition as described above, wherein the niobium nanoparticles by mass preferably comprise at least 41% crystallinity, preferably at least 61% crystallinity, and even more preferably at least 80% crystallinity.

[0062] The cosmetic composition as described above comprises up to 10% by weight of niobium nanoparticles. In one embodiment, the composition comprises 5% to 10% by weight of niobium nanoparticles.

[0063] In one embodiment, the composition consists of particles dispersed in an oil phase comprising the ingredients / excipients.

[0064] The cosmetic composition as described above, wherein the niobium nanoparticles are composed of niobium pentoxide, and its particle size distribution is: d10 = 142 nm to 197 nm, d50 = 208 nm to 343 nm, d90 = 350 nm to 599 nm; d10 = 80 nm to 129 nm, d50 = 125 nm to 247 nm, d90 = 230 nm to 435 nm.

[0065] The cosmetic composition as described above has high light protection ability.

[0066] The cosmetic composition as described above has high light protection ability against UV radiation.

[0067] A method for surface light protection, comprising at least one step of applying the cosmetic composition as defined above on at least one surface.

[0068] The method for surface light protection as described above, wherein the light protection is against UV radiation.

[0069] Use of the premix as described above for the production of a cosmetic composition for light protection against UV radiation on the individual's skin surface.

[0070] Analysis of the Nanoparticles Used in Example 1 - Example

[0071] Particle size distribution analysis was performed on niobium pentoxide nanoparticle samples with processing times (grinding) of 1 h, 6 h, and 12 h (in the cases of 6 h and 12 h, designated as LN10 6h and LN10 12h, respectively), which were used in the following examples.

[0072] The data showed that crystallinity (%) and grain size (nm) exhibited exponential decay, and the grain size (nm) seemed to reach an apparent steady state after 6 h of grinding. The decrease in crystallinity showed a behavior similar to that of the grain size. However, throughout the process of exposing niobium pentoxide particles to high-energy grinding, the crystallinity still showed significant changes. For crystallinity, about 61% of the monoclinic phase was observed in the sample ground for 1 h, about 41% of the monoclinic phase was observed in the sample ground for 6 h, and about 26% of the monoclinic phase was observed in the sample ground for 12 h. More details regarding the method used to obtain the nanoparticles can be found in the patent application BR112023003019 of the inventors of the present application.

[0073] Samples with more amorphous characteristics (e.g., the 12 h sample) showed even more significant improvements in enhancing the properties of cosmetic compositions (with about 26% crystallinity). On the other hand, significant effects were also observed in the samples ground for 1 h and 6 h (with about 41% and 61% crystallinity, respectively).

[0074] Figure 1 The results of the particle size distribution analysis of the sample with a processing time of 1 h in terms of the counting frequency (%) by diameter (nm) are shown.

[0075] Figure 2 The results of the particle size distribution analysis of the sample with a processing time of 3 h in terms of the counting frequency (%) by diameter (nm) are shown.

[0076] Figure 3 The results of the particle size distribution analysis of the sample with a processing time of 6 h in terms of the counting frequency (%) by diameter (nm) are shown.

[0077] Figure 4 The results of the particle size distribution analysis of the sample with a processing time of 12 h in terms of the counting frequency (%) by diameter (nm) are shown.

[0078] Table 1 below shows the parameters of the particle size distribution analysis (numerical distribution) of the niobium pentoxide nanoparticle sample with a processing time of 6 h.

[0079] Table 1 - Analysis Parameters of the 6 h Sample

[0080]

[0081]

[0082] Table 2 shows the results of the particle size distribution analysis (numerical distribution) of the niobium pentoxide nanoparticle sample with a processing time of 6 h.

[0083] Table 2 - Analysis results of the 6-h sample.

[0084] Concentration 0.0001% Period 1.000 Uniformity 0.315 Specific surface area <![CDATA[4140m 2 / kg]]> D[3;2] 0.315μm D[4;3] 0.375μm Dn(10) 0.142μm Dn(50) 0.208μm Dn(90) 0.350μm

[0085] Figure 5 Shows the results of the particle size distribution analysis of the sample with a processing time of 6 h in terms of the percentage of number density (%) by size category (μm).

[0086] Table 3 details the data Figure 5 that is the basis of the figure in

[0087] Table 3 - Figure 5 Data (numerical %) from the analysis of the 6-h sample in

[0088]

[0089]

[0090]

[0091]

[0092]

[0093] The following Table 4 shows the parameters of the particle size distribution analysis (volume distribution) of the niobium pentoxide nanoparticle sample with a processing time of 6 h.

[0094] Table 4 - Analysis parameters of the 6-h sample.

[0095] Particle refractive index 2.080 Particle absorption index 0.010 Dispersant name Water Dispersant refractive index 1.330 Scattering model Mie Analysis model General purpose Weighted residual 1.75% Laser shielding 2.45%

[0096] Table 5 shows the results of the particle size distribution analysis (volume distribution) of the niobium pentoxide nanoparticle sample with a processing time of 6 h.

[0097] Table 5 - Analysis results of the 6-h sample.

[0098]

[0099]

[0100] Figure 6 Shows the results of the particle size distribution analysis of the sample with a processing time of 6 h in terms of the percentage of volume density (%) by size category (μm).

[0101] Table 6 details the dataFigure 6 Basic data of the middle figure.

[0102] Table 6- Figure 6 Data for the 6h sample analysis (volume %) in the middle

[0103]

[0104]

[0105]

[0106]

[0107] The following Table 7 shows the parameters of the particle size distribution analysis (numerical distribution) of the niobium pentoxide nanoparticle sample with a processing time of 12h.

[0108] Table 7 - Analysis parameters of the 12h sample.

[0109] Particle refractive index 2.080 Particle absorption index 0.010 Dispersant name Water Dispersant refractive index 1.330 Scattering model Mie Analysis model General purpose Weighted residual 1.91% Laser shielding 2.26%

[0110] Table 8 shows the results of the particle size distribution analysis (numerical distribution) of the niobium pentoxide nanoparticle sample with a processing time of 12h.

[0111] Table 8 - Analysis results of the 12h sample.

[0112]

[0113]

[0114] Figure 7 Shows the results of the particle size distribution analysis of the sample with a processing time of 12h in terms of the percentage of number density (%) by size category (μm).

[0115] Table 9 details the data that is the basis for Figure 7 the middle figure.

[0116] Table 9 - Figure 7 Data for the 12h sample analysis (numerical %) in the middle

[0117]

[0118]

[0119]

[0120]

[0121] The following Table 10 shows the parameters of the particle size distribution analysis (volume distribution) of the niobium pentoxide nanoparticle sample with a processing time of 12h.

[0122] Table 10 - Analysis parameters of the 12h sample.

[0123] Particle refractive index 2.080 Particle absorption index 0.010 Dispersant name Water Dispersant refractive index 1.330 Scattering model Mie Analysis model General purpose Weighted residual 1.91% Laser shielding 2.26%

[0124] Table 11 shows the results of the particle size distribution analysis (volume distribution) of the niobium pentoxide nanoparticle sample with a processing time of 12h.

[0125] Table 11 - Analysis results of the 12h sample.

[0126]

[0127]

[0128] Figure 8 Shows the results of the particle size distribution analysis of the sample with a processing time of 12h in terms of the percentage of volume density (%) by size category (μm).

[0129] Table 12 details the data that is the basis for Figure 8 the figure in the middle.

[0130] Table 12 - Figure 8 Data (volume %) analyzed for the 12h sample in the middle

[0131]

[0132]

[0133]

[0134]

[0135] Example 2 - Comparison of particle size distribution analysis

[0136] Figure 9 Shows the comparison results between the curves of the niobium pentoxide nanoparticle sample with a processing time of 6h obtained by comparing the numerical distribution and the volume distribution as described in Example 1.

[0137] Figure 10 Shows the comparison results between the curves of the niobium pentoxide nanoparticle sample with a processing time of 12h obtained by comparing the numerical distribution and the volume distribution as described in Example 2.

[0138] Figure 11 Shows the comparison results between the number density curves (%) of the niobium pentoxide nanoparticle samples with processing times of 6h and 12h obtained by comparing the numerical distribution at 6h and the numerical distribution at 12h as described in Example 1.

[0139] Figure 12 Shows the comparison results between the volume density curves (%) of niobium pentoxide nanoparticle samples with treatment times of 6 h and 12 h obtained by comparing the volume distribution with a treatment time of 6 h and the numerical distribution with a treatment time of 12 h as described in Example 1.

[0140] Example 3 - Evaluation of UVA and UVB protection factors

[0141] The determination of the UVA protection factor (UVPF) using a spectrophotometric method was initially described by BL Diffey and J. Robson and later modified and adjusted by COLIPA to evaluate the protection of the skin against UVA rays provided by a product. The method described in this example consists of: using a substrate suitable for applying the sample and evaluating the UVA protection provided by the product by a spectrophotometric method. This test is based on the measurement of the transmittance of UV radiation by the sample applied to a suitable substrate with a controlled roughness. The sample is exposed to a defined and controlled level of UV radiation using an irradiation source specified by the COLIPA method. Since there may be differences in results between laboratories, in vivo SPF is used to perform a mathematical correction of the radiation transmittance spectrum by a multiplication factor C.

[0142] The sunscreen sample is exposed to a radiation dose proportional to the initial UVA protection factor (FPUVA0), which is calculated using the transmission data of the unexposed sample. The corrected transmission data of the sample exposed to UV radiation is used to calculate the final UVA protection factor (FPUVA). The method consists of: measuring the UV radiation flux through the product, which is expressed as transmittance, and comparing it with the initial UV radiation flux of the substrate without the product according to the spectrophotometric principle below:

[0143] T(λ) = I / IO, where λ is the wavelength

[0144] The relationship between absorbance and transmittance at a given wavelength λ is as follows:

[0145] A(λ) = -log(T(λ))

[0146] The absorbance values are multiplied by different irradiances and action spectra to subsequently seek a correlation with the biological response obtained by in vivo methods. The following is used to calculate the SPF: Radiation source. Spectral irradiance I(λ) generated by the UV light source. Action spectrum related to the skin reaction. Erythema-related action spectrum representing the relationship between the skin / subcutaneous reaction and the light energy E(λ) (defined by the CIE (International Commission on Illumination)). To calculate the FPUVA: Irradiation source. Spectral irradiance I(λ) generated by the UV light source. Action spectrum related to the skin reaction. Persistent pigment darkening (PPD)-related action spectrum representing the relationship between the skin / subcutaneous reaction and the light energy P(λ) in the region from 320 nm to 400 nm. I(λ), E(λ), and P(λ) are known and their values are predetermined. The UVA protection factor (UVPF) is determined by the following steps:

[0147] Step 1: Before any UV radiation, measure the in vitro absorbance A0(λ) of the product applied to the PMMA substrate.

[0148] Step 2: Mathematically correct the initial UV spectrum using the "C" coefficient so that the in vitro SPF of the test sample is equal to the in vivo SPF. Next, calculate the initial UVA protection factor (FPUVA0) using A0(λ) and C.

[0149] Step 3: Calculate the single UV dose, which is proportional to FPUVA0. (D = FPUVA0 x 1.2 J.cm -2 )

[0150] Step 4: Irradiate the sample with UV according to the calculated dose D.

[0151] Step 5: Measure the in vitro absorbance of the product after UV exposure. Obtain the second UV absorption spectrum - A(λ) data.

[0152] Step 6: Mathematically correct the second spectrum (the spectrum after exposure to UV radiation) according to the same "C" coefficient determined previously in Step 2. Then, calculate the in vitro UVA protection factor (UVFP).

[0153] In this example, one of the objectives is to evaluate the behavior of sunscreen in terms of UVA protection effectiveness using a protocol based on the ISO 24443:2012 in vitro standard for UVA photoprotection of sunscreen.

[0154] In this example, the products tested are shown in Tables 13 to 18 below.

[0155] Table 13 - 10% LN1000412 H5 Emulsion

[0156] Component / CAS# Weight % Water (7732-18-5) 59.30 Caprylic / capric triglyceride (73398-61-5 / 65381-09-1) 10.00 Niobium pentoxide premix 10.00 Undecane (1120-21-4) 7.00 Tridecane (629-50-5) 3.00 Propylene glycol (504-63-2 / 26264-14-2) 3.00 Potassium cetyl phosphate (84861-79-0 / 19035-79-1) 2.50 Glycerin (56-81-5) 2.00 Cetyl alcohol (36653-82-4) 1.25 Xanthan gum (11138-66-2) 0.70 Hydroxyacetophenone (99-93-4) 0.50 1,2-Hexanediol (6920-22-5) 0.25 Caprylyl glycol (1117-86-8) 0.25 Disodium EDTA (139-33-3 / 6381-92-6) 0.10 Tocopheryl acetate (7695-91-2 / 58-95-7) 0.10 Sodium hydroxide (1310-73-2) 0.05

[0157] Table 14 - 5% LN100046H Emulsion

[0158]

[0159]

[0160] Table 15 - 5% Zinc Oxide Emulsion

[0161] Component / CAS# Weight % Water (7732-18-5) 60.75 Caprylic / capric triglyceride (73398-61-5 / 65381-09-1) 10.00 Undecane (1120-21-4) 7.00 Zinc oxide / triethoxysilane (1314-13-2 / 2943-75-1) 5.00 Tridecane (629-50-5) 3.00 Propylene glycol (504-63-2 / 26264-14-2) 3.00 Potassium cetyl phosphate (84861-79-0 / 19035-79-1) 5.00 Glycerin (56-81-5) 2.00 Cetyl alcohol (36653-82-4) 2.50 Xanthan gum (11138-66-2) 0.70 Hydroxyacetophenone (99-93-4) 0.50 1,2-Hexanediol (6920-22-5) 0.25 Caprylyl glycol (1117-86-8) 0.25 Disodium EDTA (139-33-3 / 6381-92-6) 0.10 Tocopheryl acetate (7695-91-2 / 58-95-7) 0.10 Sodium hydroxide (1310-73-2) 0.05

[0162] Table 16 - 5% Nano - Hydroxyapatite Emulsion

[0163] Component / CAS# Weight % Water (7732-18-5) 60.75 Caprylic / capric triglyceride (73398-61-5 / 65381-09-1) 10.00 Undecane (1120-21-4) 7.00 Hydroxyapatite (1306-06-05) 5.00 Tridecane (629-50-5) 3.00 Propylene Glycol (504-63-2 / 26264-14-2) 3.00 Potassium Cetyl Phosphate (84861-79-0 / 19035-79-1) 5.00 Glycerin (56-81-5) 2.00 Cetyl Alcohol (36653-82-4) 2.50 Xanthan Gum (11138-66-2) 0.50 Hydroxyacetophenone (99-93-4) 0.50 1,2-Hexanediol (6920-22-5) 0.25 Caprylyl Glycol (1117-86-8) 0.25 Disodium EDTA (139-33-3 / 6381-92-6) 0.10 Tocopheryl Acetate (7695-91-2 / 58-95-7) 0.10 Sodium Hydroxide (1310-73-2) 0.05

[0164] Table 17 - 5% Titanium Dioxide Emulsion

[0165]

[0166]

[0167] Table 18 - 5% LN1000412H Emulsion

[0168] Ingredient / CAS# wt% Water (7732-18-5) 64.80 Caprylic / Capric Triglyceride (73398-61-5 / 65381-09-1) 10.00 Niobium Pentoxide Premix 5.00 Undecane (1120-21-4) 7.00 Tridecane (629-50-5) 3.00 Propylene Glycol (504-63-2 / 26264-14-2) 3.00 Potassium Cetyl Phosphate (84861-79-0 / 19035-79-1) 2.50 Glycerin (56-81-5) 2.00 Cetyl Alcohol (36653-82-4) 1.25 Xanthan Gum (11138-66-2) 0.20 Hydroxyacetophenone (99-93-4) 0.50 1,2-Hexanediol (6920-22-5) 0.25 Caprylyl Glycol (1117-86-8) 0.25 Disodium EDTA (139-33-3 / 6381-92-6) 0.10 Tocopheryl Acetate (7695-91-2 / 58-95-7) 0.10 Sodium Hydroxide (1310-73-2) 0.05

[0169] Samples of each product are stored in for 1 month until the testing is completed. The test product is applied to a substrate: the substrate is the material on which the sample is applied. It must be non - fluorescent, light - stable, non - reactive, and compatible with all components in the formulation. Additionally, it must enable the distribution of the product to be similar to that on human skin, and thus, it must have a textured surface. For this method, a PMMA (polymethyl methacrylate HD6 - Helioplate) plate with a textured substrate on one side is used. Each product is applied to the substrate as droplets evenly distributed along the plate at a rate of 1.3 mg / cm 2 . Then, the product is spread in a standardized manner using a finger protected by a disposable latex finger cot until a uniform film is obtained. Then, the sample is dried at room temperature in the dark for at least 30 minutes and then read. A PMMA plate coated with 5 mg of glycerol is used to record the spectrophotometer baseline.

[0170] Testing procedure. The plate is pre - irradiated. The single radiation dose is calculated based on the FPUVA0 value. During the UV radiation exposure, the sample is kept below 40°C.

[0171] Readings are taken at different positions on each PMMA plate to ensure that at least 2 cm 2The PFUVA0 or FPUVA of the plate is calculated by the average absorbance at all positions on the same PMMA plate. If the coefficient of variation of the absorbance at different positions exceeds 50%, the plate is discarded and a new plate is prepared. The FPUVA0 or FPUVA of the product is the mean of the FPUVA0 or FPUVA of at least 3 individual plates. If the coefficient of variation between the FPUVA0 or FPUVA of individual plates exceeds 20%, a new plate is prepared until the coefficient of variation meets the standard. Calculate the critical wavelength: The value of the critical wavelength (λc) of the test product is defined as the wavelength at which the area under the absorption spectrum of the irradiated product from 290 nm to λc is 90% of the total area of the absorption spectrum from 290 nm to 400 nm, and is calculated as follows: Calculate a series of absorbance values (depending on the wavelength increment) for each of the three plates to which the test product has been applied. The corresponding product results for Tables 13 to 18 are shown in Table 19 to Table 24 below.

[0172] Table 19a - Results of 10% LN10 004 6 H5 emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0173]

[0174] t - statistic: 3.182446

[0175] Number of plates: 4

[0176] CI95: 0.918693

[0177] % of CI relative to the mean: 16.7

[0178] The results obtained for the test standard are shown in Table 19b below (standard: S2, UVA - PF specification 10.7 to 14.7)

[0179] Table 19b - Results of the standard

[0180]

[0181] t - statistic: 3.182446

[0182] Number of plates: 4

[0183] CI95: 1.299228

[0184] % of CI relative to the mean: 10.8

[0185] Product 10% LN100046H emulsion, coded IPC.2022.3314, with an average UVA protection coefficient (FPUVA) of 5.5 and a critical wavelength of 382.8 nm.

[0186] Results of 20 - 5% LN1000406 H Emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0187]

[0188] t - statistic: 3.182446

[0189] Number of plates: 4

[0190] CI95: 0.795612

[0191] % of CI relative to the mean: 18.7

[0192] The results obtained from testing the standard are shown in Table 19b.

[0193] Product 5% LN100046H Emulsion, coded IPC.2022.3315, with an average UVA protection factor (FPUVA) of 4.3 and a critical wavelength of 381.3 nm.

[0194] Results of 21 - 5% Zinc Oxide Emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0195]

[0196] t - statistic: 3.182446

[0197] Number of plates: 4

[0198] CI95: 0

[0199] % of CI relative to the mean: 0

[0200] The results obtained from testing the standard are shown in Table 19b.

[0201] Product 5% Zinc Oxide Emulsion, coded IPC.2022.3316, with an average UVA protection factor (FPUVA) of 4.0 and a critical wavelength of 381.3 nm.

[0202] Results of 22 - 5% Nano - Hydroxyapatite Emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0203]

[0204]

[0205] t - statistic: 3.182446

[0206] Number of plates: 4

[0207] CI95: 0.795612

[0208] % CI relative to the mean: 24.5

[0209] The results obtained with the test reference are shown in Table 19b.

[0210] Product 5% nano-hydroxyapatite emulsion, coded IPC.2022.3317, with an average UVA protection factor (FPUVA) of 3.3 and a critical wavelength of 374 nm.

[0211] Table 23 - Results for 5% titanium dioxide emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0212]

[0213] t statistic: 3.182446

[0214] Number of plates: 4

[0215] CI95: 0.918693

[0216] % CI relative to the mean: 20.4

[0217] The results obtained with the test reference are shown in Table 19b.

[0218] Product 5% titanium dioxide emulsion, coded IPC.2022.3318, with an average UVA protection factor (FPUVA) of 4.5 and a critical wavelength of 382.8 nm.

[0219] Table 24 - Results for 5% LN10 004 12 H emulsion (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0220]

[0221] t statistic: 3.182446

[0222] Number of plates: 4

[0223] CI95: 0795612

[0224] % CI relative to the mean: 18.7

[0225] The results obtained with the test reference are shown in Table 19b.

[0226] Product 5% LN10 004 12 H emulsion, coded IPC.2022.3316, with an average UVA protection factor (FPUVA) of 4.8 and a critical wavelength of 382 nm.

[0227] Example 4 - Evaluation of the sun protection factor

[0228] The solar spectrum consists of a series of radiations, and almost all of them can play a beneficial role. However, when the amount of absorbed energy is higher than the tolerance dose, risks are inevitable. The main solar radiations are as follows: infrared rays, responsible for the heat sensation and dehydration of the skin during sun exposure; UVA (320 nm to 400 nm), which causes surface tanning; however, due to long-term sun exposure, they lead to premature skin aging; they can penetrate the most common glass. Depending on the skin thickness, they can reach the dermal tissue, making them as dangerous as higher energy wavelengths (UVB). The UVA range can be subdivided into: low UVA (320 nm to 340 nm), responsible for most of the physiological effects of UVA on the skin; and high UVA (340 nm to 400 nm), responsible for very small changes in elastic fibers; UVB (290 nm to 320 nm) is considered more harmful than UVA radiation. They can hardly penetrate the skin, but due to their high energy, they are most responsible for the direct damage and most of the delayed damage caused by solar radiation. They are also responsible for converting epidermal ergosterol into vitamin D. When in excess, they cause erythema (sunburn), premature aging, and skin cancer, mainly affecting people with fair skin; UVC (100 nm to 290 nm) is very harmful, does not stimulate tanning, but causes sunburn and cancer. Some studies have found that CFCs (chlorofluorocarbons), a group of gases that were until recently used as propellants in aerosols and refrigeration, slowly destroy the ozone layer. The consequences of this destruction have not been fully evaluated, but there is no doubt that they will have a huge impact on life on Earth. Tanning is a defense against solar radiation, which stimulates the body to produce melanin (the natural skin pigment), thus reducing the penetration of UVA and UVB radiation. During the first few days of sun exposure, the melanogenesis mechanism begins to be activated. During this period, sunscreen with a higher protection factor should be used because their function is similar to melanin, filtering UVA and UVB rays. The purpose of the sun protection factor or SPF is to show consumers the level of protection provided by the product. The great variability of solar radiation and different skin types require consumers to understand their own skin and determine which SPF is most suitable for their situation. The higher the SPF value, the higher the level of protection. To select an SPF compatible with a certain skin type, the parts of the body most easily exposed to the sun, such as the arms or face, should not be considered because these areas are directly and continuously exposed to sunlight and thus have different responses to the effects of sunlight. The SPF measurement method is based on the appearance of erythema on the skin. Therefore, it is necessary to standardize the means of measuring this erythema. Thus, the minimal erythema dose (MED) is defined as the amount of energy required to observe the first obvious erythema reaction with clearly defined boundaries 16 to 24 hours after exposure to ultraviolet radiation. The minimal erythema dose (MED) depends on the individual's skin type, the amount of melanin in the skin, and the wavelength and intensity of the incident wave.Individuals can be divided into six groups, which are also known as phototypes and are estimated based on an individual's history of sunburn and tanning after exposure to midday sunlight for 30 to 50 minutes and after a period of non-exposure. The phototypes have the characteristics described in Table 25.

[0229] Table 25 - Skin phototypes according to M.A, Patahak (1983):

[0230]

[0231] SPF corresponds to the amount of MED that a person can be exposed to sunlight without developing erythema. Therefore, SPF is defined as the ratio of the amount of ultraviolet energy required to produce an erythema dose on protected skin to the energy required to produce an erythema dose on unprotected skin.

[0232] In this example, the purpose of the test is to determine the static sun protection factor (SPF) of the test product using a protocol based on ISO 24444:2019 - Cosmetics - Sun protection test methods - In vivo sun protection factor (SPF) determination.

[0233] The selection of participants was based on the following criteria: the number of participants included in the study, 3 phototypes (Fitzpatrick) I to III, both male and female, aged 21 to 46 years.

[0234] Inclusion criteria: aged 18 to 65 years; phototypes I to III; both male and female; individual type angle (ITA°) greater than 28° - determined by colorimetry.

[0235] Inclusion / Exclusion Criteria: Skin marks in the experimental area that interfere with the evaluation of possible skin reactions (pigmentation disorders, vascular malformations, scars, increased hair growth, numerous freckles and moles, sunburn); active skin diseases (local and disseminated) that may interfere with the study results; pregnant or lactating women; a history of allergic reactions, irritation, or strong discomfort to topical products (cosmetics and drugs); participants with a history of allergy to the materials used in the study; a history of specific reactions; a history of exacerbation or induction due to ultraviolet radiation; immunodeficient individuals; those who have received kidney, heart, or liver transplants; those who have had intense sun exposure or tanning up to 15 days before the initial evaluation; those who are expected to have intense sun exposure or tanning during the study; those who are expected to bathe in the sea, swimming pool, or sauna during the study; participants who engage in water sports; those who have used the following systemic topical medications up to two weeks before selection: immunosuppressants, antihistamines, non-steroidal anti-inflammatory drugs, and corticosteroids; those who have been treated orally or topically with acidic vitamin A and / or its derivatives up to 1 month before the start of the study; those who are expected to receive a vaccine during the study or up to 3 weeks before the study; those who are participating in other studies; any circumstances that the researcher believes may impair the study evaluation and are not mentioned above; a history of non-compliance or unwillingness to comply with the study protocol; professional personnel directly involved in the implementation of this protocol and their families.

[0236] Restrictions on Participants: No cosmetic or skin treatments are to be performed during the study.

[0237] Medications Prohibited during the Study: Anti-inflammatory drugs; antihistamines; immunosuppressants; acidic vitamin A and derivatives.

[0238] Products according to Tables 13 and 18 of Example 3 are used in the test.

[0239] Consent of Research Participants. The purpose and methods of the study were explained to the participants, and they signed a free and informed consent form.

[0240] Procedure for Determining Static SPF (Dry). A multi-port 601 device, with a 300W xenon arc lamp (SolarLight CoInc); a PMA2103 SUV LLG detector; a PMA2100 photometer / radiometer. Determination of the Minimal Erythema Dose (MED).

[0241] The Minimal Erythema Dose (MED) is considered to be the amount of radiant energy required to produce the least and most obvious erythema upon evaluation 16 to 24 hours after exposure. The MED for each participant is determined by a series of ultraviolet light exposures, where the intensity (MED / minute) increases in a geometric progression, increasing by 12% (1.12n) with each exposure compared to the previous one. After irradiation for 16 to 24 hours, a local skin examination is performed to check the points of erythema appearance.

[0242] Determination of static SPF (dry). On the back (subscapular region) of each participant, a rectangle of 5.0 x 7.0 cm (35 cm 2 ) is marked with a surgical pen and is called the location. These locations are cleaned with dry cotton. At the demarcated locations, 2 mg / cm 2 of the sample to be evaluated or the standard product is applied and evenly spread with a finger wrapped with a finger cot. After application, the participant waits for 15 minutes to dry. After drying, the locations are irradiated considering the defined time of individual MED and the expected SPF of the product. Local skin examination is performed 16 to 24 hours after irradiation to determine the SPF.

[0243] SPF calculation. The SPF value is defined by the ratio of the time required to produce MED (MEDp) on skin protected with a sunscreen product to the time required to produce MED (MEDu) on unprotected skin. Therefore, the SPF value is calculated according to Equation 1.

[0244]

[0245] The SPF value is calculated for each participant. For the group of participants, the average SPF, standard deviation, and lower limit of the 95% confidence interval are calculated. Tables 26 to 31 show the results (SPF from 13.7 to 18.5) obtained for the product samples in Tables 13 to 18 and the standard product P2.

[0246] Results of the product samples in Table 26 - Table 13. Number of participants included: 3; Number of participants who completed the study: 3.

[0247]

[0248]

[0249] The average static SPF of the test product in the above table is 15.4. The average static SPF of the simultaneously evaluated standard product P2 is 16.0. These results are in line with ISO protocol 24444:2019 - Cosmetics - Methods of sun protection testing - In vivo determination of sun protection factor (SPF).

[0250] Product 10% LN100046H emulsion, coded IPC.2022.3314, has an average static SPF of 15.4.

[0251] Results of the product samples in Table 27 - Table 18. Number of participants included: 3; Number of participants who completed the study: 3.

[0252]

[0253] The average static SPF of the test products in the above table was 10.3. The average static SPF of the standard product P2 evaluated simultaneously was 16.0. These results are in line with ISO method 24444:2019 - Cosmetics - Sunscreen test methods - In vivo determination of the sun protection factor (SPF).

[0254] The product is 5% LN100046H emulsion, coded IPC.2022.3315, and its average static SPF is 10.3.

[0255] Example 5 - UVA - B SPF effectiveness compared with commercial filters

[0256] In this example, a comparative SPF UVA - B effectiveness screening was carried out between LN10 6h and LN10 12h materials and the inorganic commercial filters titanium dioxide, zinc oxide, and nano - hydroxyapatite.

[0257] The screened SPF UVA (320 nm to 400 nm) and static SPF reflect the protection level of a cosmetic product against UVB rays (290 nm to 320 nm) after application to dry skin, with a minimum drying time of 15 minutes. Tests were carried out using concentrations similar to those used in the physical sunscreen market to determine the estimated protection factors for the 6 - hour and 12 - hour versions of LN10.

[0258] UVA rays are characterized by causing the skin surface to tan and leading to premature aging of the skin due to long - term sun exposure. These rays penetrate common glass. Depending on the skin thickness, they can reach the dermal tissue, making them as dangerous as higher - energy wavelengths (UVB). The UVA range can be subdivided into: low UVA (320 nm to 340 nm), which is responsible for most of the physiological effects of UVA on the skin; and high UVA (340 nm to 400 nm), which is responsible for very small changes in elastic fibers; UVB rays (290 nm to 320 nm) are considered more harmful than UVA radiation. They can hardly penetrate the skin, but due to their high energy, they are most responsible for the direct damage and most of the delayed damage caused by solar radiation. They are also responsible for converting epidermal ergosterol into vitamin D. When in excess, they can cause erythema (sunburn), premature aging, and skin cancer, mainly affecting fair - skinned people.

[0259] For the research involved, it was decided to conduct comparative tests with nano - sized micronized titanium dioxide, zinc oxide, and nano - hydroxyapatite at a concentration of 5% (% solids). These ingredients are the most widely used physical or inorganic sunscreens in the market. To understand whether there is a proportional relationship between the application concentration and the sun protection factor, LN10 6h and LN10 12h were also tested at a concentration of 10% (% solids).

[0260] Method: A standard substrate compatible with all applications was produced for the test preparation, as detailed in the clinical test report. For this substrate, the surfactants and emollients commonly used in photoprotective preparations were listed. The active ingredients LN106h and LN10 12h were shown in the form of suspensions in an aqueous medium, and for both, the active ingredient percentage was calculated considering a solid concentration of 20%.

[0261] The results can be summarized in Table 28.

[0262] Table 28 - Results of FPUVA, FPUVB, and SPF

[0263]

[0264]

[0265] *Ultraviolet A protection factor

[0266] **Ultraviolet B protection factor

[0267] ***Sun protection factor

[0268] The results are very promising. Figure 13 An overview of the results is shown, where 5% nano-hydroxyapatite has the lowest absorption of UVA radiation and 10% LN10 has the highest absorption of UVB (static SPF).

[0269] In contrast, the results of all active ingredients applied at 5% can be seen in Figure 14 where it can be seen that titanium dioxide shows the best results for UVB absorption (FPUVB = 13.4) and UVA absorption (FPUVA = 4.5), but for UVA, the difference from the LN10 6h and LN10 12h samples (both with FPUVA = 4.3) is very small (+0.2 FPUVA percentage points), and this result is better than zinc oxide and nano-hydroxyapatite.

[0270] In Figure 15 it can be seen that in the samples of the products LN10 6h and LN10 12h, the results of the samples applied at 5% are very similar, while in the samples applied at 10%, better performance of LN1012h is observed. The FPUVA ratio of the two LN10 samples is at least 1 / 3 of FPUVB, which complies with the Brazilian regulation RDC#30 issued by Anvisa on June 1, 2012, which describes the technical regulations for sunscreen in Mercosur cosmetics. Based on the data obtained for LN10 12h, there are strong indications that each percentage point corresponds to 2 FPUVB percentage points.

[0271] The results obtained led us to conclude that LN10 at 10% active substance concentration for 12 h is more promising than LN10 at 10% active substance concentration for 6 h. For the comparative concentration of 5%, the effects of both LN10 samples are only poorer relative to titanium dioxide, but slightly superior in performance relative to zinc oxide and nano-hydroxyapatite. These results indicate that LN10 is a very promising physical sunscreen material.

[0272] Example 6 - Comparison of Micron-Sized Niobium Particle Samples

[0273] For comparison purposes, preparations with micron-sized niobium pentoxide particles (d10 to d100 = 26.2 μm to 144 μm) at amounts of 5% and 10% of the composition were also tested.

[0274] Table 29 - Sample IPC.2023.1682 - 5% Micron Nb Particles

[0275]

[0276]

[0277] Table 30 - Sample IPC.2023.1683 - 10% Micron Nb Particles

[0278]

[0279]

[0280] Using the same method as in Example 3, the UVA protection factor (UVPF) of the samples described in Tables 29 and 30 was determined.

[0281] Table 31a - Results of Sample IPC.2023.1682 - 5% Micron Nb Particles (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0282]

[0283] t statistic: 3.18

[0284] Number of plates: 4

[0285] CI95: 0.795612

[0286] % of CI relative to the mean: 18.72

[0287] The results obtained from testing the standard are shown in Table 31b below (standard: S2, UVA-PF specification is 10.7 to 14.7)

[0288] Table 31b - Results of the Standard

[0289]

[0290] t-statistic: 3.182446

[0291] Number of plates: 4

[0292] CI95: 2.002245

[0293] % of CI relative to the mean: 15.7

[0294] The average UVA protection coefficient (FPUVA) of sample IPC.2023.1682 - 5% micron Nb particles is 4.25, and the critical wavelength is 377.0 nm.

[0295] Table 32a - Results of sample IPC.2023.1683 - 10% micron Nb particles (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0296]

[0297] t-statistic: 3.18

[0298] Number of plates: 4

[0299] CI95: 0.918693

[0300] % of CI relative to the mean: 10.81

[0301] The results obtained from testing the reference standard are shown in Table 31b below (reference standard: S2, UVA - PF specification is 10.7 to 14.7)

[0302] Table 31b - Results of the reference standard

[0303]

[0304] t-statistic: 3.182446

[0305] Number of plates: 4

[0306] CI95: 2.002245

[0307] % of CI relative to the mean: 15.7

[0308] The average UVA protection coefficient (FPUVA) of sample IPC.2023.1683 - 10% micron Nb particles is 8.5, and the critical wavelength is 378.0 nm.

[0309] In addition, using the same method as in Example 4, the sun protection factors of the samples described in Tables 29 and 30 were evaluated.

[0310] Table 33 - Results for Sample IPC.2023.1682 - 5% Micron Nb Particles (Table 29). Number of Participants Included: 10; Number of Participants Who Completed the Study: 10.

[0311]

[0312]

[0313] The average static SPF of the tested samples was 12.7. The average static SPF of the standard product P2 evaluated at the same time was 15.3. These results are in accordance with ISO protocol 24444:2019 - Cosmetics - Sunscreen test methods - In vivo sun protection factor (SPF) determination.

[0314] Table 34 - Results for Sample IPC.2023.1683 - 10% Micron Nb Particles (Table 30).

[0315] Number of participants included: 10; Number of participants who completed the study: 10.

[0316]

[0317]

[0318] The average static SPF of the test samples was 23.8. The average static SPF of the standard product P2 evaluated at the same time was 16.2. These results are in accordance with ISO protocol 24444:2019 - Cosmetics - Sunscreen test methods - In vivo sun protection factor (SPF) determination.

[0319] Example 7 - Comparison of Submicron Size Niobium Particle Samples

[0320] For comparative purposes, formulations having submicron sized niobium pentoxide particles (d10 to d100 = 0.3 μm to 5.2 μm) in amounts of 5% and 10% of the composition were also tested.

[0321] Table 35 - Sample IPC.2023.1163 - 5% Submicron Nb Particles

[0322] Ingredient / CAS# wt% Water (7732-18-5) 60.39 Caprylic / Capric Triglyceride (73398-61-5 / 65381-09-1) 10.00 Submicron Niobium Pentoxide Premix 5.00 Octyl Cocoate 5.00 Undecane (1120-21-4) 3.50 Propylene Glycol (504-63-2 / 26264-14-2) 3.00 Cetyl Alcohol (36653-82-4) 3.00 Glycerin (56-81-5) 2.00 Cetearyl Olivate 1.80 Tridecane (629-50-5) 1.50 Sorbitan Olivate (223706-40-9) 1.20 Cetearyl Alcohol (67762-27-0) 0.80 Cetyl Palmitate (540-10-3) 0.60 Hydroxyacetophenone (99-93-4) 0.50 Hydroxyethyl Cellulose 0.50 Sorbitan Palmitate (5050-91-9) 0.40 Sorbitan Oleate (1338-43-8) 0.20 1,2-Hexanediol (6920-22-5) 0.25 Caprylyl Glycol (1117-86-8) 0.25

[0323] Table 36 - Sample IPC.2023.1162 - 10% Submicron Nb Particles

[0324]

[0325]

[0326] Using the same method as in Example 3, the UVA protection factor (UVPF) of the samples described in Tables 35 and 36 was determined.

[0327] Table 37a - Results of Sample IPC.2023.1163 - Sub - micron 5% Nb Particles (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0328]

[0329]

[0330] t - statistic: 3.182446

[0331] Number of plates: 4

[0332] CI95: 2.002245

[0333] % of CI relative to the mean: 15.7

[0334] The results obtained for the test standard are shown in Table 37b below (Standard: S2, UVA - PF specification from 10.7 to 14.7)

[0335] Table 37b - Results of the Standard

[0336]

[0337] t - statistic: 3.182446

[0338] Number of plates: 4

[0339] CI95: 2.002245

[0340] % of CI relative to the mean: 15.7

[0341] The average UVA protection factor (FPUVA) of Sample IPC.2023.1163 - 5% Sub - micron Nb Particles is 6.5, and the critical wavelength is 378.0 nm.

[0342] Table 38a - Results of Sample IPC.2023.1162 - Sub - micron 10% Nb Particles (where λc corresponds to the critical wavelength; SD is the standard deviation):

[0343]

[0344]

[0345] t - statistic: 3.18

[0346] Number of plates: 4

[0347] CI95: 0.795612

[0348] % of CI relative to the mean: 9.09

[0349] The results obtained with the test reference product are shown in Table 38b below (reference product: S2, UVA-PF specification from 10.7 to 14.7).

[0350] Table 38b - Results for the reference product

[0351]

[0352] t statistic: 3.182446

[0353] Number of plates: 4

[0354] CI95: 2.002245

[0355] % of CI relative to the mean: 15.7

[0356] The average UVA protection factor (FPUVA) of the sample IPC.2023.1162 - 10% submicron Nb particles is 8.75 and the critical wavelength is 379.0 nm.

[0357] Furthermore, using the same method as in Example 4, the sun protection factors of the samples described in Tables 35 and 36 were evaluated.

[0358] Table 39 - Results for the sample IPC.2023.1163 - 5% submicron Nb particles (Table 35).

[0359] Number of participants included: 3; Number of participants who completed the study: 3.

[0360]

[0361] The average static SPF of the test sample is 13.4. The average static SPF of the reference product P2 evaluated simultaneously is 16.4. These results are in accordance with ISO protocol 24444:2019 - Cosmetics - Sun protection test methods - In vivo determination of the sun protection factor (SPF).

[0362] Table 40 - Results for the sample IPC.2023.1162 - 10% submicron Nb particles (Table 36). Number of participants included: 10; Number of participants who completed the study: 10.

[0363]

[0364] The average static SPF of the test sample is 23.5. The average static SPF of the reference product P2 evaluated simultaneously is 16.4. These results are in accordance with ISO protocol 24444:2019 - Cosmetics - Sun protection test methods - In vivo determination of the sun protection factor (SPF).

[0365] Example 8 - Overall comparison table

[0366] For comparison purposes, Figure 17 Figure showing a comparison of all the formulations tested in the present invention.

[0367] Table 41 - Comparative table of in vitro UVA protection and SPF of the test formulations.

[0368]

[0369]

[0370] Based on the above results, for formulations containing 5% by mass of particles, when compared with a composition containing 5% by mass of titanium dioxide (which is commonly used in sunscreen), it can be observed that for compositions containing niobium pentoxide particles ground for 1 h, 6 h, and 12 h at 5%, particularly better results than titanium dioxide are observed. Especially in the case where the solid particles are dispersed in the oil phase.

[0371] Similarly, for compositions containing niobium pentoxide particles ground for 12 h, particularly expressive results are observed at a higher concentration (e.g., 10% by mass). However, for niobium pentoxide particles ground for 1 h, 6 h, and particles with micron and sub - micron diameters, very expressive results are also observed at high concentrations. For the 1 h, 6 h, and 12 h particles, especially in the case where the solid particles are dispersed in the oil phase.

[0372] Especially for formulations containing particles with micron diameters, an exfoliating effect is observed.

[0373] When the applicant submits this application to the competent authority, he / she undertakes, attempts, and aims to: (i) attribute the authorship to the author / inventor with respect to the moral, copyright, and property rights related to his / her work; (ii) clearly indicate that he / she is the holder of a trade secret or industrial secret, and any form of intellectual property derived therefrom and the holder desired by the applicant; (iii) describe in detail the content of the creation and the secret, demonstrating its existence in both the physical and legal environments; (iv) obtain protection for his / her mental creation in accordance with the provisions of the Copyright Law; (v) establish the relationship between the examples / embodiments and the creative, decorative, unique, or inventive concept based on the applicant's knowledge and his / her background, in order to clearly show the scope of his / her protected and / or protectable intangible assets; (vi) request and obtain the additional rights stipulated by the patent if the applicant chooses to continue the administrative procedure until the end.

[0374] Any future disclosure or publication of this document shall not, in itself, constitute an authorization for third-party commercial use. Even if the content becomes part of the physical world accessible to third parties, the publication of this document in accordance with legal provisions does not eliminate its confidential legal status. Merely and solely as a matter of legal spirit, for the purposes of: (i) serving as proof that the creator created the object described herein and expressed it in a physical medium (i.e., this report itself); (ii) clearly indicating its right holder / holder and author / inventor; (iii) declaring to third parties the creation and the existence of the trade secret, as well as the content of the intellectual property protection (including patent protection) or the content for which intellectual property protection (including patent protection) is to be requested and its filing date, from which date priority will be obtained and the patent exclusivity period (if applicable) may commence; (iv) assisting the country's technological and economic development based on the disclosure of the creation, and if this occurs, authorizing the use of the secret only in exceptional cases for the purpose of research and / or development of new improvements, so as to avoid parallel reinvestment by third parties in developing the same assets.

[0375] It is hereby noted that any commercial use shall require authorization from the author or the right holder / holder, and unauthorized use will be subject to legal sanctions. In this context, given the large number of details of the creation, concept, and embodiments disclosed by the applicant, those skilled in the art will be able to implement other ways of implementing this creation and / or invention in a manner that is not exactly the same as the manner illustrated above by way of example only without undue effort. However, such forms are considered or may be considered to fall within the scope of one or more of the appended claims.

Claims

1. A premix for producing a cosmetic composition, characterized in that, It contains one or more excipients and a certain mass of niobium nanoparticles, wherein the mass of the niobium nanoparticles contains at least 26% crystallinity.

2. The premix according to claim 1, characterized in that, The mass of the niobium nanoparticles preferably contains at least 41% crystallinity, preferably contains at least 61% crystallinity, and even more preferably contains at least 80% crystallinity.

3. The premix according to claim 1, characterized in that, It contains up to 80% by weight of niobium nanoparticles.

4. A method for producing a cosmetic composition, characterized in that, It includes at least one step of mixing the premix defined in claim 1 with a cosmetic excipient.

5. A cosmetic composition, characterized in that, It contains one or more excipients and a certain mass of niobium nanoparticles, wherein the mass of the niobium nanoparticles contains at least 26% crystallinity.

6. The cosmetic composition according to claim 5, characterized in that, The mass of the niobium nanoparticles preferably contains at least 41% crystallinity, preferably contains at least 61% crystallinity, and even more preferably contains at least 80% crystallinity.

7. The cosmetic composition according to claim 5, characterized in that, It contains up to 10% by weight of niobium nanoparticles.

8. The cosmetic composition according to claim 5, characterized in that, It has high light protection ability.

9. The cosmetic composition according to claim 8, characterized in that, It has high light protection ability against UV radiation.

10. A method for surface light protection, characterized in that, It includes at least one step of applying the cosmetic composition defined in claim 5 to at least one surface.

11. The method for surface light protection according to claim 10, characterized in that, The light protection is against UV radiation.

12. Use of the premix defined in claim 1, characterized in that, It is used for preparing a cosmetic composition for light protection against UV radiation on the skin surface of an individual.

Citation Information

Patent Citations

  • NIOBIUM NANOPARTICLE PREPARATION, USE AND PROCESS FOR OBTAINING IT

    BR112023003019

  • Dispersed powder providing sun protection suitable for use in cosmetic composition

    JP2003267850A

  • NANO-particles for cosmetic applications

    WO2007133808A2

  • Metal complexes of macrocycles and / or isoprenoids and / or linear tetrapyrroles by mechanochemistry (grinding or milling), preparation method thereof, sunscreen / concealer / UV absorber thereof, self-assembled coating material thereof, superamphiphilic material or surfaces thereof, hair dyeing thereof and other uses thereof

    WO2021121647A1